Muscular strength training and its effect on strength endurance and speed in wheelchair tennis players - Azeez, Sumayah Riyadh; Majeed, Widad Kadhim (SPORT TK-EuroAmerican Journal of Sport Sciences, 2022)
The primary aim of this study was to prepare muscular strength exercises to develop the endurance of the arms and the speed for wheelchair tennis players. The players of the Iraqi national team of wheelchair tennis constituted the research community for the present study. A total of 5 players registered in the records of the Iraqi Federation of Racquet Games, who were training and competing in the sports season 2020/2021, were recruited as the participants of the study. A total of 24 training units were included in the study with two units/week for total of 12 weeks. The researchers concluded that the muscular strength training significantly improved the strength endurance and the speed of the wheelchair tennis players.